Sustainable parking management strategy for Sultan Ahmad Shah Mosque, Kuantan - Asfidayu, Abdul Ghani (2012)
Parking facility can be considered as part of planning requirement that can affect development scheme as a whole. The increasing of population of a town parallel with the increase of road users lead to parking concerns, especially around the Sultan Alimad Shah Mosque, Kuantan. The mosque is a sacred place for the Muslim, however, the car parking problem at Masjid Sultan Ahmad Kuantan is a, long-standing issue that tarnished the image of the Mosque. These problems occur because it is located around the business central such as banking, administration area and also as a center of Muslims meeting. The problem occurred because a limited number of parking spaces that can be used by patrons. The public complaint of insufficient car park and traffic congestion occurred in that area, and this study is conducted to identify the factors that contribute to the problem. The demand for parking at the Sultan Ahmad Shah Mosque is critical during Friday prayer. Therefore the main objective of this study is to evaluate the efficiency of the parking lots by various methods.